Implementation of SKI Learning Media in Increasing Student Motivation and Learning Outcomes - Mohammad Saat Ibnu Waqfin; Alfiyatul Khoiriyah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The process of delivering teaching materials or materials really needs media assistance to make it more attractive, efficient, practical, and effective in delivering teaching materials and knowledge information, as well as having an appeal for students to pay attention to and understand the learning material being conveyed. This study aims to find out how the implementation of learning models using learning media in the form of audio-visual in increasing motivation and student learning outcomes of XI MA Darun Najah Ngijo-Karangploso Malang in SKI subjects. This qualitative-descriptive research was conducted following a research flow consisting of the stages of preparation, implementation, observation, and reflection. The research data were obtained using library and field study techniques and were carried out continuously. This research proves that the use of learning media in the form of audio-visual can increase the motivation and learning of class XI MA Darun Najah students, especially in SKI subjects. However, in practice, there are some students who have not been able to achieve the learning target.